“ENTERING LIFE” OF POETRY BY E.T.A. HOFFMANN AND GÜNTER GRASS - Etaryan, Yelena (2021)
In this scientific article, it is assumed that the literary works of the Nobel Prize laureate and the German national poet Günter Grass are characterized by romantic features. For this reason, the novel Ein weites Feld (“A Wide Field”) by Grass and the fairy tale Der goldene Topf (“The Golden Pot”) by E.T.A. Hoffmann are examined in terms of their similarities and differences. It is noteworthy that E.T.A. Hoffmann has so far only been associated with Grass in relation to his fairy tale “Klein Zaches, called Zinnober”, and the main hero of the fairy tale served as a literary model for Oskar Matzerath from “The Tin Drum”. Thus, this article makes it possible to throw a new light on Grass’es research. In this paper the following aspects are analyzed: questions of poetics, genesis, main characters, narrative or fictional levels, structural principles, as well as the role of the reader. The results are summarized in the final part of the investigation.